Incorporating The Influence of Regional Culture in Tableware Design: The Case Study of Chaoshan Area - Zhuopeng, Li; Muhammad Jameel, Mohamed Kamil (Penerbit Universiti Sains Malaysia, 2023)
Tableware has traditionally played a significant part in China’s food culture and has a high usage rate as a product directly tied to everyday life. Therefore, designing tableware with local cultural characteristics may aid in the education of people to appreciate local culture. However, there is a considerable shortage of research on tableware with Chaoshan cultural elements. Hence, this research will include both Chaoshan culture and tableware design. It is recommended that Chaoshan culture be employed as a design element in tableware design, and that the viability of using tableware as a carrier to express regional culture be explored. The significance of this study will aid in improving the Chaoshan region’s cultural production, boosting cultural confidence, and increasing local revenues.